Safety and Effectiveness of Tailored Hemorrhoidectomy in Outpatients Setting - Tomasicchio, Giovanni; Martines, Gennaro; Lantone, Giuliano; Dibra, Rigers; Trigiante, Giuseppe; De Fazio, Michele; Picciariello, Arcangelo; Altomare, Donato Francesco; Rinaldi, Marcella (Frontiers in Surgery, 2021)
Introduction: Single or double prolapsed pile instead of full muco-hemorrhoidal prolapse is a common finding in patients with symptomatic III or IV degree hemorrhoids. For this selected group of patients, relief of symptoms could be achieved by managing the single/double prolapsed piles instead of performing traditional hemorrhoidectomy. The aim of this single-center study was to evaluate the safety and medium- and long-term effectiveness of an outpatient tailored Milligan-Morgan hemorrhoidectomy (MMH) performed under local anesthesia (LA). Material and methods: Clinical records of 202 patients submitted to outpatient tailored MMH, under LA and without anal dilation, treated between 2013 and 2020, were retrospectively reviewed using a prospectively maintained database and completed by a telephone interview or outpatient consultation. Postoperative pain score, the need for painkillers, postoperative complications and symptoms recurrence, return to working activities, and patient grading assessment scale were recorded. Results: Thirty-five (17%) out of 202 patients recruited were lost to the follow-up. One hundred and fifty-two and 15 patients underwent a single and double pile hemorrhoidectomy, respectively. With regard to postoperative outcomes, visual analogue scale (VAS) decreased from a median value of 4 [interquartile range (IQR) 2–6] on the day of surgery to 1 (IQR 0–4) on the 10th postoperative day (p < 0.001). Sixty-one patients (37%) needed oral painkillers during the 1st week after surgery. There was no mortality or major postoperative complication. Bleeding requiring hospital readmission was reported in seven (4%) patients, and one patient underwent emergency surgery with no need for blood transfusion. No postoperative urinary retention, anal incontinence, or stricture occurred in the series. During the median follow-up of 39 (IQR 12–60) months, 26 patients (16%) reported symptoms of recurrence but only six underwent traditional MMH. Recovery to normal activity occurred within a median period of 6 days (IQR 3–10) and the Clinical Patient Grading Assessment Scale (CPGAS) at 1 year after surgery was reported to be a “good deal better.” Conclusions: Tailored MMH performed under LA in an ambulatory setting can be considered a safe and effective technique with high compliance and satisfaction of patients.